Pelatihan Penyusunan Modul Ajar Berbasis Proyek bagi Guru SMA di Kawasan Perbatasan Indonesia – Malaysia - Budiman, Jumardi; Ulfah, Maria; Purwaningsih, Endang; Achmadi, Achmadi; Okianna, Okianna; Wiyono, Hadi; Adlika, Nur Meily (Jurnal Pengabdian Kepada Masyarakat, 2025)
As a result of initial observations and interviews with high school principals in Sekayam District, there are still some teachers who have difficulties in implementing the independent curriculum and are not proficient in compiling PjBL modules, especially teachers in the Indonesia-Malaysia border area. Based on this phenomenon, the team agreed to conduct counseling activities on training on the preparation of project-based teaching modules for high school teachers in the Indonesia - Malaysia border area. The reason for the selection of high school teachers in border areas as targets for PKM activities is the lack of continuous training and assistance from the government and other parties so that the lack of teacher skills to adapt to changes in education policy. The method of implementing this PKM is in the form of counseling on the independent curriculum and the preparation of project-based learning modules. The results of the PKM show that participants have increased knowledge and have the initial ability to design project-based learning modules.